Clinical Practices for Measles-Mumps-Rubella Vaccination Among US Pediatric International Travelers - Hyle, Emily P. (JAMA Pediatr, 2019)
IMPORTANCE: The US population is experiencing a resurgence of measles, with more than 1000 cases during the first 6 months of 2019. Imported measles cases among returning international travelers are the source of most US measles outbreaks, and these importations can be reduced with pretravel measles-mumps-rubella (MMR) vaccination of pediatric travelers. Although it is estimated that children account for less than 10% of US international travelers, pediatric travelers account for 47% of all known measles importations. OBJECTIVE: To examine clinical practice regarding MMR vaccination of pediatric international travelers and to identify reasons for nonvaccination of pediatric travelers identified as MMR eligible. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study of pediatric travelers (ages ≥6 months and <18 years) attending pretravel consultation at 29 sites associated with Global TravEpiNet (GTEN), a Centers for Disease Control and Prevention–supported consortium of clinical sites that provide pretravel consultations, was performed from January 1, 2009, through December 31, 2018. MAIN OUTCOMES AND MEASURES: Measles-mumps-rubella vaccination among MMR vaccination–eligible pediatric travelers. RESULTS: Of 14 602 pretravel consultations for pediatric international travelers, 2864 travelers (19.6%; 1475 [51.5%] males; 1389 [48.5%] females) were eligible to receive pretravel MMR vaccination at the time of the consultation: 365 of 398 infants aged 6 to 12 months (91.7%), 2161 of 3623 preschool-aged travelers aged 1 to 6 years (59.6%), and 338 of 10 581 school-aged travelers aged 6 to 18 years (3.2%). Of 2864 total MMR vaccination–eligible travelers, 1182 (41.3%) received the MMR vaccine and 1682 (58.7%) did not. The MMR vaccination–eligible travelers who did not receive vaccine included 161 of 365 infants (44.1%), 1222 of 2161 preschool-aged travelers (56.5%), and 299 of 338 school-aged travelers (88.5%). We observed a diversity of clinical practice at different GTEN sites. In multivariable analysis, MMR vaccination–eligible pediatric travelers were less likely to be vaccinated at the pretravel consultation if they were school-aged (model 1: odds ratio [OR], 0.32 [95% CI, 0.24-0.42; P < .001]; model 2: OR, 0.26 [95% CI, 0.14-0.47; P < .001]) or evaluated at specific GTEN sites (South: OR, 0.06 [95% CI, 0.01-0.52; P < .001]; West: OR, 0.10 [95% CI, 0.02-0.47; P < .001]). The most common reasons for nonvaccination were clinician decision not to administer MMR vaccine (621 of 1682 travelers [36.9%]) and guardian refusal (612 [36.4%]). CONCLUSIONS AND RELEVANCE: Although most infant and preschool-aged travelers evaluated at GTEN sites were eligible for pretravel MMR vaccination, only 41.3% were vaccinated during pretravel consultation, mostly because of clinician decision or guardian refusal. Strategies may be needed to improve MMR vaccination among pediatric travelers and to reduce measles importations and outbreaks in the United States.